Inter-enterprise Business Transaction Management in Open Service Ecosystems - Kutvonen, L.; Norta, A.; Ruohomaa, S. (2012 IEEE 16th International Enterprise Distributed Object Computing Conference, 2012)
One of the difficult challenges in inter-enterprise computing is aligning business transactions and technical management of distributed transactions, especially in breach situations. We propose and analyse a two-level business transaction management framework that allows injection of business level concerns to the control processes of inter-enterprise transactions. The two levels are associated with a) the metamodel of the collaboration, captured in eContract governing the collaboration, and b) the transactional interactions between collaboration member services. The two levels are bound together to form a reflective model, while business level breaches to the eContract can disturb the normal interactions, the metalevel possesses processes for managing (rolling back, compensating, ignoring, triggering ecosystem-level consequences) the failure in manners that align with the business incentives. This framework enables correctness, coherence and efficiency of processing in open inter-enterprise environments, i.e., service ecosystems.